2023
DOI: 10.1002/ccr3.7101
|View full text |Cite
|
Sign up to set email alerts
|

“All‐on‐4” and “All‐on‐6” treatment concept applied using computer‐guided surgery in a patient: Case report with a 2‐year follow‐up

Abstract: This case aimed to assess the clinical and radiographic outcomes of the All‐on‐4 and the All‐on‐6 concept using three‐dimensional computer‐assisted treatment planning, and computer‐guided surgery. Two years after the treatment, the “All‐on‐4” and “All‐on‐6” concepts provided effective treatment for immediate restoration and showed predictable outcomes in a completely edentulous patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Following meticulous 3D virtual planning, data pertaining to the optimal positioning and inclination of the implants were meticulously analyzed. This analysis facilitated the fabrication of template surgical-precision resin cylindrical guides featuring titanium perforations (Figure 2), fixed and stabilised with the help of fixation screws, ensuring precise implant placement during the surgical procedure for the maxilla [10]. The surgery was performed under local anesthesia, were placed 6 implants for the upper jaw in the regions 15, 14, 12, 22, 24, 26 and 6 implants for the lower jaw in the regions 46, 44, 42, 31, 34, 36.…”
Section: Case Reportmentioning
confidence: 99%
“…Following meticulous 3D virtual planning, data pertaining to the optimal positioning and inclination of the implants were meticulously analyzed. This analysis facilitated the fabrication of template surgical-precision resin cylindrical guides featuring titanium perforations (Figure 2), fixed and stabilised with the help of fixation screws, ensuring precise implant placement during the surgical procedure for the maxilla [10]. The surgery was performed under local anesthesia, were placed 6 implants for the upper jaw in the regions 15, 14, 12, 22, 24, 26 and 6 implants for the lower jaw in the regions 46, 44, 42, 31, 34, 36.…”
Section: Case Reportmentioning
confidence: 99%
“…Furthermore, most studies are case reports (Bolding & Reebye, 2022; Mozer, 2020), compare previous findings with a small sample size (Chen, Al‐Taezi, et al., 2023; Yang et al., 2023) or are in vitro studies (Chen, Bai, et al., 2023; Tao et al., 2022), in which the clinical factors cannot be completely reproduced or calculated, such as jaw tremors, saliva and bleeding, limited mouth opening and real bone reaction to the surgery (Bai et al., 2021; Parra‐Tresserra et al., 2021). Studies have shown that implant accuracy in in vivo trials is lower than in in vitro and ex vivo models, especially in apical global and axial deviations (Albaqawi, 2023; Bover‐Ramos et al., 2018).…”
Section: Introductionmentioning
confidence: 99%